Survey on Reliability of Language Achievers: Exploring the validity and scoring methods of language achievers test (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The total time required foradministering the test is 35 minutes in addition to the time necessary forgiving instructions. Picture Construction Activity; this action presents thesubject with two easy geometrical figures, a semi-circle and a rhombus andrequires him to construct an elaborate picture using each figure as an integralpart. Originality and elaboration are emphasized to make novel picture and givedetails as he thinks necessary. 10 minutes are allowed for the two tasks. Thetitles may also be scored for verbal elaboration and originality and the scoresadded to the verbal achievers score obtained on the verbal achievers test. Thescoring of titles, however, is optional. Picture construction has long been used as a measure of child’s creativethinking. Torrance has used this test in his battery of achievers tests but ina slightly different manner. Here the subject is provided with a fixedstructure, which he can convert into meaningful picture, by building on his ownimagination.  Incomplete Figures Activity; this activityconsists of 10 line drawings which could be made into meaningful pictures ofdifferent objects. The subject is asked to make a picture, which no one else inthe group will be able to think of. The subject is given 15 minutes for the 10items. Each item is scored for elaboration and originality. Triangles andEllipses Activity; in this activity the subject is provided with 7 trianglesand 7 ellipsis and he is required to construct different meaningful picturesbased on the two given stimuli. As the subject is here encouraged” to makemultiple associations to single stimuli” the responses could be scored also forelaboration and originality. The author of the test suggests that the test usershould confine him to elaboration and originality scoring alone. A total timeof 10 minutes is allowed for this activity.